2009
DOI: 10.1097/ajp.0b013e3181934276
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Gastric-retentive Gabapentin for the Treatment of Postherpetic Neuralgia

Abstract: Gabapentin ER administered twice daily is effective and safe for the treatment of pain associated with postherpetic neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 25 publications
2
65
0
1
Order By: Relevance
“…Although other trials [49][50][51][52] had shown clinical efficacy of gabapentin at dosages of 600 --3600 mg (gabapentin enacarbil) daily for treatment of PHN, the results of pain relief were not consistently reported [53] and the optimal dose of gabapentin for PHN is inconsistent [54]. It is thought that divided-dose and oncedaily extended release gabapentin (gabapentin enacarbil) has exerted these different clinical outcomes [49,53]; therefore, Fan et al [48] conducted a meta-analysis on all eligible (six randomized controlled trials) to assess the efficacy and safety of gabapentin 1800 mg/d treatment compared to placebo for PHN. This analysis showed that gabapentin 1800 mg treatment results in a significant improvement in 24-h average pain intensity scores, sleep rating scores (which implies improvement in quality of life) and an improvement in Patient Global Impression of Change and Clinician Global Impression of Change compared to placebo in patients with PHN up to 14 weeks (range 4 --14 weeks, [49,52],).…”
Section: Efficacy and Safety Of Gabapentin In The Treatment Of Phnmentioning
confidence: 97%
“…Although other trials [49][50][51][52] had shown clinical efficacy of gabapentin at dosages of 600 --3600 mg (gabapentin enacarbil) daily for treatment of PHN, the results of pain relief were not consistently reported [53] and the optimal dose of gabapentin for PHN is inconsistent [54]. It is thought that divided-dose and oncedaily extended release gabapentin (gabapentin enacarbil) has exerted these different clinical outcomes [49,53]; therefore, Fan et al [48] conducted a meta-analysis on all eligible (six randomized controlled trials) to assess the efficacy and safety of gabapentin 1800 mg/d treatment compared to placebo for PHN. This analysis showed that gabapentin 1800 mg treatment results in a significant improvement in 24-h average pain intensity scores, sleep rating scores (which implies improvement in quality of life) and an improvement in Patient Global Impression of Change and Clinician Global Impression of Change compared to placebo in patients with PHN up to 14 weeks (range 4 --14 weeks, [49,52],).…”
Section: Efficacy and Safety Of Gabapentin In The Treatment Of Phnmentioning
confidence: 97%
“…The only exception was peripheral edema, which had a higher incidence over 24 weeks (8.8%) than was observed in the 2, 10-week studies (3.2% and 5%). 19,20 Although no direct comparative studies with gabapentin tid have been performed, the incidences of both dizziness and somnolence in patients treated with G-GR 1800 mg/d over 24 weeks were lower than those reported in short-term trials with gabapentin 600 mg tid, 6,7 whereas the incidence of peripheral edema was similar. Although no other long-term safety data for gabapentin in patients with PHN were found, gabapentin has been administered for Z6 months to patients with epilepsy, fibromyalgia, and pain after spinal cord injury.…”
Section: Resultsmentioning
confidence: 81%
“…17,18 Previous short-term (r10 wk) studies with G-GR, administered once or twice daily, for the management of PHN showed a low incidence of AEs, particularly dizziness and somnolence. [19][20][21] The current study evaluated the longterm safety and tolerability of G-GR and its effect on weight gain in PHN patients treated with G-GR for a total of 24 weeks.…”
mentioning
confidence: 99%
“…A recent randomized, double-blind, placebo-controlled study evaluated gastric-retentive gabapentin in patients with chronic pain from postherpetic neuralgia, with statistically signifi cant reductions in pain scores in the gabapentin ER twice-daily group. However, pain scores in the once-daily gabapentin group were not reduced more than those in the placebo group [ 25 ].…”
Section: A Brief Survey Of Novel Analgesicsmentioning
confidence: 98%